Pro-environmental behavior in Singapore : effectiveness of commitment and information - Tan, Li Qin (2014)
This study sought to uncover the current environmental attitudes and behaviors of Singaporeans, and to examine the effectiveness of commitment and informational strategies in raising levels of pro-environmental behavior (PEB) in Singapore. The study involved two phases – a street survey, and an online survey delivered two weeks later. In the street survey, participants (N = 208; 107 male; median age = 21-25) completed a questionnaire containing one of six manipulations – control, commitment, specific information, general information, commitment plus specific information, and commitment plus general information. Results showed that in terms of environmental attitudes, participants had a more positive green worldview (M = 3.87, SD = 0.61) than green consumption attitudes (M = 3.35, SD = 0.64). As for environmental behaviors, participants more frequently performed resource limitation behaviors (M = 3.68, SD = 0.71) in comparison to green consumer behaviors (M = 2.89, SD = 0.77). The study failed to support the hypothesis that commitment coupled with specific informational strategies would be effective in raising levels of PEB, F(10, 60) = 1.56, p = .14, ns. The replication of certain general findings in the attitudinal and conservation psychological literature addresses the important concern of generalizability voiced by other researchers (Schultz, Oskamp, & Mainieri, 1995; Henrich, Heine, & Norenzayan, 2010; Schultz, 2014). Practical implications for people who are concerned about raising levels of PEB in Singapore are discussed.